ASPEK-ASPEK KINERJA DALAM ISLAM - Suryani, Eli (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2014)
Mu’amalah objects in Islamic terminology is very broad, so Koran and sunnah explain more on muamalah issues in global and universal language that demand active interpretation of Moslem. This fact is actually an indication that Islam provides an opportunity for people to do their own innovation and new creations to do mu’amalah activity in accordance with the importance of their needs as long as the form of muamalah are not againts the basic foundations of Islamic teachings. One of the many practices of mu’amalah done by today’s modern society is what is known as an employment system or employment contract, or in terms of the classical fiqh it is called alIjarah. For the clearer goal of this discussion it is necessary to determine the thinking framework about the concept of Ijarah and its foundation used. Study on this article found that Islam sets regulation on the employment relationships traffic arrangements for the employment relationship in mutual way: what becomes the right for one side and vice versa. This reciprocal relationship is manifested in the form of employment agreement. The aspects that must exist in the employment agreement or contract between the employee and employer are working conditions, working hours, and wages determination. While employee’ rights are the right to receive decent wage, the right to get the job according to ability, the right for health services, and the right for legal protection.